2009
DOI: 10.1111/j.1365-2044.2009.05915.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound vs nerve stimulation multiple injection technique for posterior popliteal sciatic nerve block

Abstract: SummaryIn this prospective, randomised, observer-blinded study we evaluated whether ultrasound guidance can shorten the onset time of popliteal sciatic nerve block as compared to nerve stimulation with a multiple injection technique. Forty-four ASA I-III patients undergoing posterior popliteal sciatic nerve block with 20 ml of 0.75% ropivacaine were randomly allocated to nerve stimulation or ultrasound guided nerve block. A blinded observer recorded onset of sensory and motor blocks, success rates, the need fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 21 publications
1
61
1
3
Order By: Relevance
“…A total of 508 articles were rejected for the following reasons: 448 did not evaluate ultrasound-guided nerve blocks in surgical procedures, 30 were not RCTs, 24 did not compare ultrasound alone versus control, 5 did not assess upper or lower extremity single-shot nerve blocks, and one did not assess surgical success rate. Table 1 provides a detailed overview of the studies included in the analysis [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 508 articles were rejected for the following reasons: 448 did not evaluate ultrasound-guided nerve blocks in surgical procedures, 30 were not RCTs, 24 did not compare ultrasound alone versus control, 5 did not assess upper or lower extremity single-shot nerve blocks, and one did not assess surgical success rate. Table 1 provides a detailed overview of the studies included in the analysis [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In their recent systematic review, Munirama and McLeod [15] reported no difference in postoperative neurological side effects, though they reported a reduced incidence of analgesic or anaesthetic rescue in the ultrasound group. Other authors have demonstrated comparable onset times and success rates with ultrasound and nerve stimulation guidance in other types of blocks [16]. Various cited studies in a review by Griffin and Nicholls showed faster onset times for ultrasoundguided nerve blocks in different locations [17].…”
Section: Discussionmentioning
confidence: 96%
“…US-guided block offers advantages compared to traditional techniques and is becoming the common technique. It has been shown to reduce the local anesthetic volume and also the incidence of complications by visualization of the plexus brachialis and the neighboring anatomic structures (7)(8)(9)(10). When compared to peripheral nerve stimulation technique, US guidance is more effective, with less pain during awake procedures and reduces the rate of vascular puncture.…”
Section: Introductionmentioning
confidence: 99%